Cord Lining Mesenchymal Stem Cells Have a Modest Positive Effect on Angiogenesis in Hindlimb Ischemia - Chua, Kenon; Lim, Fui Ping; Lee, Victor Kwan Min; Phan, Toan Thang; Tai, Bee Choo; Tan, Yih Kai (Frontiers in Cell and Developmental Biology, 2021)
Purpose: We investigated the use of human Cord Lining Mesenchymal Stem Cells (CL-MSCs) (US Patent number 9,737,568), in a rabbit hindlimb ischemia model, and evaluated their potential in stimulating neovascularization. Allogenic human CL- MSCs could potentially be used to treat patients with lower limb ischemia and non-healing wounds. Methods: Twenty rabbits were divided into two separate groups. We created a hindlimb ischemia model surgically. At 21 and 49 days post-operatively, animals in the treatment group were injected with CL-MSCs (500,000 cells per 0.2 ml on each site) at 10 different sites (Quadriceps- 4 sites, Hamstrings- 4 sites and Calf-−2 sites) in the hindlimb muscles. The control group received only saline injection to the corresponding sites at the same time point as the treatment group. We then evaluated the effects of treatment on neovascularization by angiography, laser doppler perfusion imaging, as well as by histology. We evaluated the tissue samples for any signs of local immune reaction to the cell implantation. We also observed the rabbit clinically for any adverse effects after treatment. Results: We found a higher number of CD31 positive cells in the treatment group, with a greater number of capillaries found in the treated muscles. The Rectus Femoris demonstrated a median vessel count/muscle fiber of 0.121 for the treatment group, compared to 0.076 in the control group (median difference 0.04; 95% CI 0.001–0.11; p = 0.041). The Gastrocnemius demonstrated a median vessel count/muscle fiber of 0.175 for the treatment group, compared to 0.089 in the control group (median difference 0.087; 95% CI −0.006 to 0.234; p = 0.07). Blood perfusion quantification through Laser Doppler Perfusion Imaging (LDPI) also demonstrated a non-statistically significant increase in perfusion in favor of the treatment group. CL-MSCs demonstrated no toxicity associated morbidity and minimal local immune reaction to implantation. Conclusion: CL-MSCs have a positive effect on angiogenesis in a rabbit hindlimb ischemia model. This preliminary data is encouraging and paves the way for future large animal studies or for clinical trials.